Mutational analysis of the candidate tumor suppressor genes TEL and KIP1 in childhood acute lymphoblastic leukemia1 - Stegmaier, Kimberly; Takeuchi, Seisho; Golub, Todd R.; Bohlander, Stefan K.; Bartram, Claus R.; Koeffler, H. Phillip; Gilliland, D. Gary (Cancer research, 1996)
We have shown previously that loss of heterozygosity at chromosome band 12p13 is among the most frequent genetic abnormalities identified in acute lymphoblastic leukemia (ALL) of childhood. Two known genes map within the critically deleted region of 12p: TEL, the gene encoding a new member of the ETS family of transcription factors, which is rearranged in a variety of hematological malignancies; and KIP1, the gene encoding the cyclin-dependent kinase inhibitor p27. Both genes are, therefore, excellent candidate tumor suppressor genes. In this report, we determined the exon organization of the TEL gene and performed mutational analysis of TEL and KIP1 in 33 childhood ALL patients known to have loss of heterozygosity at this locus. No mutations in either TEL or KIP1 were found; this suggests that neither TEL nor KIP1 is the critical 12p tumor suppressor gene in childhood ALL.
Gesehen am 08.01.2024